Arabic Learning Media Based on Neuroscience - Abdul Azis; Suyadi Suyadi (Universitas Ahmad Dahlan, 2023)
Learning Arabic cannot be separated from learning media that can carry out the functions of the right brain and left brain, so learning Arabic will run effectively. This study uses a qualitative method with a library research approach. Researchers in data analysis use content analysis method where this method is carried out by identifying information objectively. The result of this discussion is that Arabic learning media that can optimize the left brain and right brain are varied. Neuroscience-based Arabic learning media. The first, using a flash card or word card media. Second, using audio-visual media. Both of these media have a function in learning listening competence, which can improve students' sense of hearing and familiarize them with receiving language input more often. In addition, this media utilizes all the purposes of language skills, namely listening, reading, writing and speaking. So that in the learning process, flash cards and audio-visual media optimize the functions of the two brains, namely the right and left brain.